Microcalcification clustering parameters in breast disease: a morphometric analysis of radiographs of excision specimens - Ng, K.H.; Looi, L.M.; Bradley, D.A. (Faculty of Medicine, University of Malaya, 1996)
X-ray microradiography of surgically excised breast specimens offers the possibility of morphological characterization of calcifications. When combined with digital imaging techniques there exists added potential for obtaining valuable basic quantitative morphometric information regarding differences between microcalcifications in tissues exhibiting evidence of fibrocystic change, benign and malignant tumours. A total of 157 excised breast specimens from 84 patients were microradiographed using a Softex Super Soft X-ray unit and Kodak AA high resolution industrial film. A Quantimet 570C image analysis system was used to digitize and analyse the microradiographs. Of the 157 microradiographs, 51 (from 30 patients) revealed microcalcification clusters. The existence of significant differences between the three identified categories of tissue were indicated by clustering parameters. These included the number of particles per cluster, area of clusters, maximum distance to nearest neighbour, and geometric mean distance to nearest neighbour. The distribution pattern index (DPI), another of the clustering parameters used in this study, has been observed to be a particularly powerful discriminator. The value for fibrocystic change was found to be significantly smaller (0.514) than that for benign tumour (0.796) whilst that for benign tumour was observed to be significantly larger than that for malignant tumour (0.604) at a p-value of less than 0.05 (Kruskal-Wallis one-way analysis of variance).